2017
DOI: 10.1161/jaha.117.006750
|View full text |Cite
|
Sign up to set email alerts
|

Subclinical Cardiac Dysfunction and Brain Health in Midlife: CARDIA (Coronary Artery Risk Development in Young Adults) Brain Magnetic Resonance Imaging Substudy

Abstract: BackgroundWe investigated whether cardiac parameters in young adulthood are associated with indicators of brain health in midlife.Methods and ResultsThis study includes 648 participants from the CARDIA (Coronary Artery Risk Development in Young Adults) study (52% women, 38% black). We studied associations of cardiac parameters assessed by echocardiography (left ventricular ejection fraction, left atrial volume, and left ventricular mass) in young adulthood (mean age: 30 years) with brain measures obtained by m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
22
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 33 publications
1
22
0
2
Order By: Relevance
“…We initially identified covariates based on previous literature as sociodemographic and health-related characteristics related to the risk of low cognitive performance and cognitive decline [1,5,[29][30][31][32][33][34]. Selected sociodemographic characteristics include age, gender (women vs. men), years of education, civil status (partner vs. no partner), employment status (currently working vs. not working), residence (urban vs. rural).…”
Section: Covariatesmentioning
confidence: 99%
“…We initially identified covariates based on previous literature as sociodemographic and health-related characteristics related to the risk of low cognitive performance and cognitive decline [1,5,[29][30][31][32][33][34]. Selected sociodemographic characteristics include age, gender (women vs. men), years of education, civil status (partner vs. no partner), employment status (currently working vs. not working), residence (urban vs. rural).…”
Section: Covariatesmentioning
confidence: 99%
“…Information on clinical and social risk factors, as potential mediators in the association of SEP with cognition, was initially identified based on the literature [24][25][26][27][28][29][30] and availability in the SHARE dataset. From those, we chose variables that were associated with the composite cognitive score at the level of p < 0.05 in at least 4 waves, after adjustment for age, sex, and years of education.…”
Section: Covariatesmentioning
confidence: 99%
“…Previous studies found that HF is associated with a damage in brain areas that could contribute to cognitive deficits, development of cognitive impairment as well as dementia including Alzheimer's disease . Worse cognitive function was observed already at early stages of left ventricular dysfunction and furthermore, even in younger people without cardiovascular disease, there was an association between subclinical cardiac dysfunction and subtle injury of the brain …”
mentioning
confidence: 98%
“…Interestingly, the study participants were on average as young as middle‐aged at the time of their first hospitalization for HF. This is of interest because the burden of HF is increasing in some subgroups of young people and therefore the strategies to prevent HF would likely have the greatest impact if applied early in life …”
mentioning
confidence: 99%
See 1 more Smart Citation